Application of transcranial brain stimulation in dementia - Yuncin Luo; Feng-Yi Yang; Raymond Y Lo (Tzu-Chi Medical Journal, 2023)
The number of patients with dementia grows rapidly as the global population ages, which posits tremendous health-care burden to the society. Only cholinesterase inhibitors and a N-methyl-D-aspartate receptor antagonist have been approved for treating patients with Alzheimer's disease (AD), and their clinical effects remained limited. Medical devices serve as an alternative therapeutic approach to modulating neural activities and enhancing cognitive function. Four major brain stimulation technologies including deep brain stimulation (DBS), transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), and transcranial ultrasound stimulation (TUS) have been applied to AD in a clinical trial setting. DBS allows electrical stimulation at the specified nucleus but remains resource-demanding, and after all, an invasive surgery; whereas TMS and tDCS are widely available and affordable but less ideal with respect to localization. The unique physical property of TUS, on the other hand, allows both thermal and mechanical energy to be transduced and focused for neuromodulation. In the context of dementia, using focused ultrasound to induce blood-brain barrier opening for delivering drugs and metabolizing amyloid protein has drawn great attention in recent years. Furthermore, low-intensity pulsed ultrasound has demonstrated its neuroprotective effects in both in vitro and in vivo studies, leading to ongoing clinical trials for AD. The potential and limitation of transcranial brain stimulation for treating patients with dementia would be discussed in this review.